Proces Laszlo Rajka jako wstęp do propagandowej rozprawy z Tito (na podstawie relacji w „Trybunie Ludu” i prasie lokalnej - Kamiński, Bruno (Acta Universitatis Lodziensis. Folia Historica, 2009)
The political trials in the Soviet bloc’s states constituted a perfect opportunity to propaganda manipulation aimed at establishing in the citizens’ consciousness desired image of reality. The trial of the Hungarian Republic’s former Minister of Foreign Affairs, Laszlo Rajk, which was conducted in September 1949 was a classic example of making use of one political actor in order to direct the burden of accusations against another political figure from outside the immediate circle of the dock. In practice, the trial of Rajk and his accomplices indicated the beginning of propaganda onslaught on the alleged instigator of a plot of the whole group - the leader of Yugoslavia, Josip Broz Tito. This trial was organized in accordance with the most elaborated native patterns of the USSR, the country which was interested in the general discrediting of Yugoslavia. This resulted from the fact that the latter state was excluded from Kominform due to its ideological and political departures from Marxist-Leninist line promoted by Moscow especially since 1947, when Kominform was established. The important element of the trial was its proper highlighting in mass media. This was the reason why the Hungarian authorities invited many journalists from socialist states and Western countries to inform about the process. These actors were supposed to be observers of the professional competence of the socialist judiciary. In reality, the journalists gathered in a courtroom were fed lies, which were professionally composed into the bill of indictment of Rajk and which referred to the crimes of Tito. The biased accounts in the socialist press were a continuation of manipulations taking place in a courtroom. Seemingly they provided the honest and detailed picture of the situation, in fact they were supposed to smuggle into consciousness of the readership a top-down established image of reality. The articles concerning Rajk’s trial, which were published in “Trybuna Ludu”, an official press organ of the PZPR constitute the prefect example of this tendency. In the accounts, the messages embedded in the text were strengthened by the special exposition and gaudy typography, what was meant to attract the attention of the reader. The analysis of the press accounts on the trial juxtaposed with the historians’ knowledge to date gives the opportunity to present the range of the press distortions and to assess the extent to which the press complied with Moscow’s directives.